1996
DOI: 10.1074/jbc.271.19.11141
|View full text |Cite
|
Sign up to set email alerts
|

Protein Misfolding and Inclusion Body Formation in Recombinant Escherichia coli Cells Overexpressing Heat-shock Proteins

Abstract: PreS2-S-␤-galactosidase, a three-domain fusion protein that aggregates extensively in the cytoplasm of Escherichia coli, was used to systematically investigate the effects of heat-shock protein (hsp) overproduction on protein misfolding and inclusion body formation. While the co-overexpression of the DnaK and DnaJ molecular chaperones led to a 3-6-fold increase in the recovery of enzymatically active preS2-S-␤-galactosidase over a wide range of growth temperatures (30 -42°C), an increase in the concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
124
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(130 citation statements)
references
References 36 publications
(45 reference statements)
5
124
0
1
Order By: Relevance
“…Our results complement previous efforts to follow protein aggregation in vivo (26)(27)(28)(29)(30). However, studies that allow direct observation of aggregation without analysis of cell constituents after lysis are rare (31,32 (33) designed an in vivo protein folding assay using N-terminal fusions to GFP to identify proteins that did not aggregate, but did not directly observe aggregation events.…”
Section: Discussionsupporting
confidence: 69%
“…Our results complement previous efforts to follow protein aggregation in vivo (26)(27)(28)(29)(30). However, studies that allow direct observation of aggregation without analysis of cell constituents after lysis are rare (31,32 (33) designed an in vivo protein folding assay using N-terminal fusions to GFP to identify proteins that did not aggregate, but did not directly observe aggregation events.…”
Section: Discussionsupporting
confidence: 69%
“…shock prior to induction, possibly due to chaperone induction (12). Adding ethanol to the growth media mimics heat-shock response in E. coli and enhances solubility of some recombinant proteins (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] The magnitude of this eŠect is variable, apparently depending on the individual target protein to be overexpressed; in this study, coexpression of groESL markedly attenuated inclusion body formation, increasing FDM levels in the cell-free extract to 80z of the total. This is theˆrst report of GroELS assisting a nicotinoprotein to assume its native structure, including its tightly bound coenzyme, in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] For instance, coexpression of molecular chaperones-a ubiquitous class of proteins that play an essential role in protein folding, especially in vivo-increases the proportion of some recombinant proteins found in their native folded structure. [9][10][11] In that regard, it was recently reported that coexpressed molecular chaperones prevent heterologous proteins expressed by E. coli clones from forming inclusion bodies. For example, the activity of Anacystis nidulans ribulose bisphosphate carboxylase was increased by the coexpression of chaperonin.…”
mentioning
confidence: 99%